Small intestinal necrosis caused by the embolism of the superior mesenteric artery after percutaneous vertebroplasty: a case report and analysis of the causes - Wenwu Zhang; Qiang Lv; Sumin Yang; Qiudong Liang (BMC Musculoskeletal Disorders)
Abstract Background Percutaneous vertebroplasty (PVP) is a minimally invasive procedure frequently employed to treat osteoporotic vertebral compression fractures in the elderly. However, bone cement leakage is a complication that cannot be completely avoided of PVP, which may lead to disastrous consequences. We present a rare case of small intestinal necrosis caused by embolism of the superior mesenteric artery following PVP. Through this case report, we aim to raise awareness among all medical professionals involved in this procedure about the importance of preventing cement leakage during PVP and to improve their skills in managing similar cases. Case presentation A 65-year-old female patient with a T12 vertebral compression fracture underwent PVP at our hospital. Subsequently, she experienced progressive and worsening abdominal pain. Abdominal computed tomography angiography (CTA) revealed linear high-density shadows in the abdominal aorta, superior mesenteric artery, renal artery, and splenic artery, along with necrosis of the right kidney, spleen, and small intestine. The patient ultimately underwent surgery to remove the necrotic small intestine and ileocecum, which confirmed that the multiple organ necrosis was caused by bone cement embolization. Conclusion If a patient experiences abdominal discomfort after PVP, a CT scan should be performed to confirm any leakage of bone cement into the abdominal vessels. Once cement leakage in the abdominal artery is identified, general surgeon should be promptly consulted for assistance. To prevent cement leakage into the abdominal artery during PVP, it is essential to carefully monitor not only the fluoroscopy results but also the patient’s condition and reactions throughout the procedure.